Knowing broadcasting (IRIB) issues in policy for corporation with new media - Abdolkarim Khayami; Seyyed Jamalaldin Hoseiny; Leila Ebad Ardestani (Religion & Communication)
The main purpose of this research is to identify broadcasting (IRIB) issues for interaction with new media. For getting the answer to research main question, the researcher has qualitativeinterview «semi-structured» with 13 people from managers and experts in cyberspace areas and broadcast making policycollageprofessor and experts in communication and media, and actives in cyberspace areas in addition to study related areas herself. In the present research, the method of «Thematic analysis» has been used and in 3 coding descriptive, interpretive and integration steps, 13 issues in 5 parts of :1-management issues: «separation of policy making chains , technical,generation content and .... of organization in cyberspace area ⸴ organizational structural inefficiency for organization outside optimized management», 2- issues arising surroundingchanges «audience change features and backward oforganization reactioninto technology changing speed and new media content», 3- issues related to rules and regulation: «plurality of country cyberspace regulatoryand Ambiguity in defining the concept  ofacquisitiveaudio and videoand its’ responsible», 4- issues arising the weakness of knowledge and proficiency: «absence of managers and policy makers’ proficiency viewpoint to cyberspace, the weakness of personal and subsistentexperience of some managers and experts in using new media, absence of futurology and forecasting and also imperfect knowledge from economic and commercial dimensionsof cyberspace» 5- and issues arising approach and viewpoint to cyberspace:«analogue and broadcast’thinkingand viewpoint conquest in different areas, imagine cyberspace management as if its somethingengineering and technicaland doubt andassumingenemy to it»were identified.